2023
DOI: 10.7759/cureus.40159
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Empathy and Its Correlates Among Indian Medical Students: A Cross-Sectional Study of Bihar

Abstract: BackgroundClinical empathy is standing in the patient's shoes and perceiving his/her emotions to experience the patient's feelings. Practicing empathy ensures an enticing prospect in patient care. This study was done among undergraduate medical students to assess their empathy level and the factors affecting it. MethodsThis was a cross-sectional study conducted with 400 medical students in Bihar, India. Students not willing to participate were excluded from the study. The coding system was designed to strictly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…The present study also found that the mean total empathy score was significantly higher for students who intended to specialize in people-oriented fields compared to those who desired to specialize in procedureoriented specialties. This finding is consistent with previous studies that have examined this relationship [10,12,21,25,28,29]. However, in the study by Chatterjee et al [20], the difference was marginally nonsignificant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study also found that the mean total empathy score was significantly higher for students who intended to specialize in people-oriented fields compared to those who desired to specialize in procedureoriented specialties. This finding is consistent with previous studies that have examined this relationship [10,12,21,25,28,29]. However, in the study by Chatterjee et al [20], the difference was marginally nonsignificant.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the comparison of mean empathy scores across the six academic years, the present study found no significant differences. These findings are consistent with those of previous studies [21][22][23]. However, our results contrast with those of Kataoka et al [26], who reported significantly higher mean total scores for students in years two, three, five, and six compared to those in year one.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is consistent with the vast majority of prior studies. Many studies conducted across various cultures reported statistically significant differences in overall empathy scores between male and female students and confirmed that female medical students are more empathetic than their male counterparts [ 10 , 14 , 15 , 16 , 17 , 25 , 29 , 33 , 37 , 55 , 57 , 58 , 60 , 62 , 63 , 64 , 66 , 67 , 68 , 69 , 76 , 83 , 84 , 89 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ]. As mentioned above, this discrepancy changes across the academic years.…”
Section: Discussionmentioning
confidence: 83%
“…This finding is in line with the minority of prior studies. Some studies confirm that undergraduate medical students who are inclined to choose “specialties that require continuous and prolonged encounters with patients” (“people-oriented” specialties, such as pediatrics, family medicine, general internal medicine, and psychiatry) receive significantly higher empathy scores than those inclined to choose specialties that do not require continuous and prolonged encounters with patients (“technology/procedure-oriented” specialties, such as pathology, radiology, anesthesiology, and surgical specialties) [ 14 , 28 , 37 , 41 , 50 , 58 , 60 , 64 , 67 , 68 , 76 , 81 , 84 , 85 , 101 , 109 ]. Luna et al combined gender and career preference and concluded: “men, preference for technology-oriented specialty, less empathy.…”
Section: Discussionmentioning
confidence: 99%